Terrorism in India - Omprakash, S.; Indian Institute of Technology Kanpur (New Delhi Ess Ess Publications, 1997)
Papers presented at a two day National Symposium on Community Issues and Interventions, organised by the Department of Humanities and Social Sciences, Indian Institute of Technology, Kanpur, and the Senior Superintendent of Police, Kanpur, on July 2 & 3, 1992
Keywords: Terrorism -- India; Gangsters -- India; Insurgency -- India